A dose‐adjusted, open‐label, pilot study of the safety, tolerability, and pharmacokinetics of STC3141 in critically ill patients with sepsis - Rinaldo Bellomo; John Patava; Ruth Van Lancker; Nathalie Layios; Marijke Peetermans; Mark Plummer; Rachid Attou; Robert McNamara; Andrew Udy; Bradley Wibrow; Adam Deane; Edward Litton; et al. (Pharmacology Research & Perspectives, 2024)
Abstract Increased circulating histones correlate with sepsis severity and are a potential therapeutic target. Pre‐clinical studies showed benefit with a histone‐neutralizing polyanion molecule (STC3141). We aimed to investigate the safety, tolerability, and pharmacokinetics of STC3141 in critically ill patients with sepsis. We studied 26 patients with sepsis divided into four cohorts of one, five, ten, and ten subjects, respectively. We conducted a dose‐adjusted, open‐label study to determine the safety, tolerability, and pharmacokinetics of STC3141 administered as an IV infusion for up to 72 h, with rate adjusted to estimated creatinine clearance. Four steady‐state concentrations were targeted. Twenty of the 26 subjects (77%) in the study experienced at least one adverse event (AE). The most frequently reported study drug‐related AE was a mildly prolonged aPTT (four events). Only one AE (pulmonary hemorrhage) led to discontinuation of the drug. After excluding patients receiving renal replacement therapy (RRT) patients, clearance ranged from 3.3 to 4.2 L/h across cohorts and was essentially completely renal in nature. Half‐life values ranged from 5 to 7 h. The mean (±SD) terminal half‐life for non‐RRT subjects and for whom it was possible to calculate was approximately 9 (±4.77) h but increased to 19 (±7.94) h for subjects on RRT. Overall, 18 (69.2%) patients completed the study to day eight in the ICU, and 22 (84.6%) survived to 28 days. STC3141 administration appeared to have an acceptable degree of safety and tolerability and expected pharmacokinetics. Cautious, larger randomized efficacy trials in sepsis appear justified.